2D Heterostructure for High‐Order Spatiotemporal Information Processing (Adv. Funct. Mater. 7/2022). (8th February 2022) - Zhai, Yongbiao; Xie, Peng; Feng, Zihao; Du, Chunyu; Han, Su‐Ting; Zhou, Ye
Abstract : Spatiotemporal Information Processing In article number 2108440, Ye Zhou and co‐workers design a 2D heterostructure‐based memtransistor to emulate the Bienenstock–Cooper–Munro theory, since such structures not only induce a spontaneous forgetting process but also offer another gate‐tunable forgetting effect. The BCM learning rule is perfectly demonstrated on this memtransistor using triplet‐STDP. Furthermore, high‐order spatiotemporal recognition is achieved in a feedforward neuron network.